Pengaruh Kepuasan Pasien dengan Prinsip-Prinsip Syariah pada Rumah Sakit XX - Syaifullah Syaifullah (Syntax Corporation Indonesia, 2024)
The purpose of this study is to test the quality system on the basis of the principles or principles implemented in RS XX. To test patient satisfaction at XX Hospital, and to test the effect of service quality quality based on sharia principles or principles on patient satisfaction at XX Hospital. This research method uses quantitative descriptive design, research that wants to show accurately, facts, characteristics, situations, or certain groups. The results of this study show that the basic concepts of Islam affect service to patient satisfaction and xx hospitals have implemented service improvement according to sharia principles, the four principles focus on rabbaniyyah, akhlaqiyyah, waqi'iyah and insaniyyah, but there are still gaps in implementation.